Nigeria giant in the tropics volume 1 : a compendium (Lagos : Gadumo, 1993)
This volume is a particularly rich and readable collection of well-researched and well-written essays on every aspect of Nigeria life, including history, culture, the arts, geography, politics, economics, defence and foreign policy. The book shows why Nigeria is unmistakably the "Giant of Africa and the Black World".
usc 03/11/2021
Ref.
Keywords: Nigeria